Generation and characterization of novel induced pluripotent stem cell (iPSC) lines derived from three symptomatic carriers of a pathogenic MYH11 variant and two non-carrier relatives - Aria Atash; Maarten Jan Cramer; Barend Mees; Pieter A. Doevendans; Joost P.G. Sluijter; Francesca Stillitano (Stem Cell Research)
A novel pathogenic variant in the MYH11 gene (c.4559+1G>A) leading to exon 32 skipping, is a rare cause of familial aortic aneurysms and dissections (fTAAD). The phenotype has proven highly variable with reduced penetrance. Here, we report human induced pluripotent stem cell (iPSC) lines, generated from peripheral blood mononuclear cells (PBMCs) of three variant carriers and two non-carrying family members. Each iPSC line exhibited typical iPSC morphology and expressed positive markers for pluripotency and tri-lineage differentiation. These cell lines offer a platform for in vitro investigation of the unknown fTAAD pathophysiology and testing of therapeutical agents for aneurysm growth attenuation.